Associative learning and conditioning theory human and non-human applications - Schachtman, Todd R.; Reilly, Steve (New York ; Oxford : Oxford University Press, 2011)
Organisms survive and succeed because of their ability to learn and adapt to changing circumstances and new demands. As discussed in the chapters of the present volume, an appreciation of the mechanisms and principles of learning and conditioning is fundamental to any analysis of normal behaviour.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Learning, Psychology of; Classical conditioning; Human behavior; Paired-association learning